Legal Politics in Restorative Justice - Indra Satria Pratama (CV. Strata Persada Academia, 2023)
This research aims to examine legal politics in restorative justice in the criminal justice system. This research is essential. After all, many obstacles are encountered because there is still no sound and comprehensive understanding of the limitations or lack of human resource capacity. This research is normative juridical normative research, with the approach tending more toward statutory and conceptual regulations. The results of this research show that implementing legal politics means holding elections to achieve the best results in criminal legislation in the sense of fulfilling the requirements of justice and being effective. The law must have a conscience. The law is not a tool to win competition but to achieve peace. He explained that the Indonesian legal system is gradually sending people to prison. The law should peacefully resolve matters that humanely, logically, and feel do not need to be brought to court or do not need to be punished severely; the law must also pay attention to the fate of the victim. For this reason, the role of authorized state bodies is needed to express justice through restorative justice.